Renal ADAM10 and 17: Their Physiological and Medical Meanings - Kato, Takashi; Hagiyama, Man; Ito, Akihiko (Frontiers in Cell and Developmental Biology, 2018)
ADAMs (a disintegrin and metalloproteinases) are a superfamily of Zn2+-dependent transmembrane and secreted metalloproteases, and consist of an N-terminal signal sequence, a prodomain, a zinc-binding metalloprotease domain, a disintegrin domain, a cysteine-rich domain, a transmembrane domain and a cytoplasmic tail. ADAMs perform proteolytic processing of the ectodomains of diverse transmembrane molecules. This review summarizes on their most known members, ADAM10 and 17, especially focusing on kidneys. ADAM10 is expressed in renal tubular cells and effects on the expression of specific brush border genes, and its activation is involved in some renal diseases. ADAM17 is weakly expressed in normal kidneys, but its expression is much induced in the tubules, capillary, glomeruli and mesangium, and involved in interstitial fibrosis and tubular atrophy. So far, the various substrates are found in the kidneys. The shedding fragments become the released ligands such as Notch and EGFR ligandsand act as the chemoattractant factor including CXCL16 respectively. Their ectodomain shedding is closely correlated with pathological factors, which include inflammation, interstitial fibrosis, and renal injury. Also, the substrates of both ADAMs contain the molecules that play important roles at the plasma membrane, for instance, meprin, E-cadherin, Klotho, and CADM1. Meanwhile, by released into urine, the shedding products could be useful for biomarkers of renal diseases, but ADAM10 and 17 per se are also notable for the biomarkers. Furthermore, ADAM10 and/or 17 inhibitions by various strategies such as small molecules, antibody, and their recombinant prodomains are valuable, because they might protect renal tissues and affect renal regeneration. Although temporal and spatial regulations of inhibitors are indispensable problems to be solved, their inhibitors could be useful for renal diseases.